Student teachers' manual for observation and participation - Corpuz, Brenda B.; Rimas, Amparo T. ;Galangco, Norma Rika S. ;Bautista, Apolinario G. (Quezon City, Philippines : Katha Publishing Co, Inc., 2002)
This manual, second edition, is a product of years of experience in handling Student Teaching. It is an attempt to help student teachers, Supervising Instructors/ Professors, Student Teaching Coordinators, and Academic Deans of teacher education institutions effectively organize their Student Teaching program particularly its first phase, Observation and Participation.
Part I. Orientation -- Part II. Observation and post observation conference.
Includes bibliographical references.
Keywords: EDUCATIONAL PSYCHOLOGY